Methode zur Einbindung realer Nutzerprofile in die ökologische und ökonomische Bewertung von Fahrzeugkonzepten - Megyesi, Péter (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2018)
The book at hand shows possibilities to derive requirements from customers' usage behaviour based on recorded vehicle data. The focus lies on the derivation of mobility and driving profiles for a computer aided calculation of the fuel consumption. On this basis, the calculated fuel consumption is integrated into the creation of life cycle assessments and total cost of ownership calculations in order to evaluate vehicle concepts.